A novel PCR-based technology for rapid and non-sequencing authentication of Bombyx batryticatus using species-specific primers. Issue 9 (3rd May 2019) - Yang, Huan; Zhou, Ying; Yu, Pingtian; Yang, Yaya; Jiao, Zhaoqun; Tam, James P.; Shen, Yuping; Jia, Xiaobin
Abstract: A novel PCR technology was developed to detect short DNA fragments using species-specific primers for rapid and non-sequencing authentication of Bombyx batryticatus based on differences in the mitochondrial genome. Three specifically designed primer reactions were established to target species for the reliable identification of their commercial products. They were confirmed to have a high inter-species specificity and intra-species stability. The limit of detection was estimated as 1 ng of genomes for Beauveria bassiana and 100 pg for Bombyx mori and Metarhizium anisopliae . Furthermore, validation results demonstrated that raw materials and their processed products can be conveniently authenticated with good sensitivity and precision using this newly proposed approach. In particular, when counterfeits were assayed, these primer sets performed well, whereas COI barcoding technology did not. These could also assist in the discrimination and identification of adulterates of other animal-derived medicines in their pulverized and processed forms and even in complexes. Abstract :